A short review on the effect of nozzle geometry in 3D printing process using FDM system - Sukindar, Nor Aiman; Md Azhar, Muhammad Afif; Ani, Mohd. Hanafi; Anuar, Hazleen; Kamaruddin, Shafie; Syed Shaharuddin, Sharifah Imihezri; Triblas Adesta, Erry Yulian (RMP Publications, 2022)
Layer-by-layer buildup of material is utilized in the process known as additive manufacturing (AM) to produce prototypes or end products. Fused deposition modelling (FDM) is one of the most commonly used AM processes. For FDM, the extruder’s nozzle plays a significant role as it is responsible for creating the build of material layer by layer. The quality and consistency of the extruded material are linked to how the material flows inside the extruder’s liquefier. Any modifications to the nozzle design directly influence the flow behaviour of the material and the final 3D printed part. The geometry of the nozzle affects the distribution of the material’s temperature, extrusion velocity, and pressure. In addition, the nozzle geometry also has an impact on the surface quality and texture of the printed material.